Effects of a crossarm brace application on a 275 KV fiberglass-reinforced polymer crossarm subjected to a lightning impulse muhammad syahmi - Rahman A.; Kadir M.Z.A.A.; Ab-Rahman M.S.; Osman M.; Nor S.F.M.; Zainuddin N.M. (MDPI AG, 2023)
Electric lines; Electric power transmission; Glass fibers; Lightning; Reinforced plastics; Transmissions; Different voltages; Fiberglass-reinforced polymers; Lightning impulse; Lightning impulse voltage; Mechanical performance; Potential distributions; Simulation studies; Transmission tower; Reinforcement